Percentile rankings and position differences for absolute and allometrically scaled performance measures from the National Football League scouting combine - Gillen, Z. M. (The Journal of Strength and Conditioning Research, 2023)
This study aimed to provide percentile rankings for absolute and allometrically scaled performance measures for National Football League (NFL) Scouting Combine subjects and determine if allometric scaling affected position-specific differences in performance measures. Subjects included American football players (n = 3,015) who participated in the NFL Scouting Combines between 2015 and 2019. Subjects were divided into position groups: defensive backs (DBs, n = 562), defensive linemen (DL, n = 498), linebackers (LBs, n = 395), offensive linemen (OL, n = 505), running backs (RBs, n = 303), tight ends (TEs, n = 165), quarterbacks (QBs, n = 165), and wide receivers (WRs, n = 422). Performance measures included 40-yd dash time (with 10- and 20-yd split times), bench press repetitions to failure, vertical jump height, broad jump distance, pro-agility time, and L-cone drill time. Descriptive statistics were computed for all performance metrics and allometrically scaled performance metrics. One-way analyses of variance tested for position group differences for absolute and allometrically scaled performance measures. Percentile rankings for absolute and allometrically scaled performance measures were determined. Position-specific differences for absolute performance measures indicated that DB and WR tended to be faster, jump higher and further, and have greater change-of-direction capabilities compared with LB, QB, RB, and TE, who scored better in these respects than OL and DL. Allometric scaling revealed that DL, LB, RB, and TE tended to have superior performance than DB and WR, with QB and OL having the poorest performance. This study provides percentile rankings and the equation and parameters by which coaches and practitioners may allometrically scale data for evaluations of normalized performance measures from the NFL Scouting Combine.